Vaginal Symptoms after Reconstructive Surgery for Prolapsed Pelvic Organ - Tahereh Eftekhar; Leila Pirzadeh; Zinat Ghanbari; Mamak Shariat (Tehran University of Medical Sciences, 2010)
Objective: Pelvic organ prolapse is a common disorder in women over the world and its general treatment is surgery. Therefore it is important to consider if vaginal symptoms, quality of life and sexual function after surgery improve. The purpose of this study was to assess vaginal symptoms in women 3 months after surgery for pelvic organ prolapse. Materials and methods: In this study 50 eligible women were evaluated between March 2007 and May 2008. These women underwent physical examination for prolapse staging and medical status and completed the ICIQ-VS questionnaire pre- and post operation 3 months later). Results: Mean age was 44.86 (31-74) years and %72 were premenopausal. Vaginal symptoms, sexual function and quality of life scores improved in order (8.88 Vs 18.04, 17.16 Vs 34.48, 2.76 Vs 4.8, all P<0.05). Conclusion: Vaginal symptoms, sexual function and quality of life after surgery improved. It appears that in Iranian patients, the performance of reconstruction surgery alone results in satisfaction.